2022
DOI: 10.15252/emmm.202216333
|View full text |Cite
|
Sign up to set email alerts
|

A type IV Autotaxin inhibitor ameliorates acute liver injury and nonalcoholic steatohepatitis

Abstract: The lysophosphatidic acid (LPA) signaling axis is an important but rather underexplored pathway in liver disease. LPA is predominantly produced by Autotaxin (ATX) that has gained significant attention with an impressive number of ATX inhibitors (type I-IV) reported. Here, we evaluated the therapeutic potential of a (yet unexplored) type IV inhibitor, Cpd17, in liver injury. We first confirmed the involvement of the ATX-LPA signaling axis in human and murine diseased livers. Then, we evaluated the effects of Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Autotaxin inhibitors reduce steatosis in hepatocytes and migration and expression of inflammation-related genes in macrophages. 27 Also, Autotaxin was reported to modulate the innate immune response in acute liver failure via lysophosphatidylcholinic acid receptors 1 and 3 in peripheral monocytes. 28 This relationship and the mechanisms involved need to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autotaxin inhibitors reduce steatosis in hepatocytes and migration and expression of inflammation-related genes in macrophages. 27 Also, Autotaxin was reported to modulate the innate immune response in acute liver failure via lysophosphatidylcholinic acid receptors 1 and 3 in peripheral monocytes. 28 This relationship and the mechanisms involved need to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 The type IV inhibitor Cpd17 ameliorates acute liver injury and nonalcoholic steatohepatitis. 27 However, no studies with ALD models have been reported. Further preclinical studies should be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell lysates were obtained by re-suspending cell pellets in RIPA buffer (50 mM Tris pH7.4, 150 mM NaCl, 1% Triton X-100) with freshly added protease inhibitor (Roche) as previously described [ 45 , 46 ]. Nuclear proteins were prepared with the NE-PER Kit (Pierce) following the manufacturer’s recommendation.…”
Section: Methodsmentioning
confidence: 99%
“… 114 , 115 Inhibition of the major lysophosphatidic acid generating enzyme autotaxin (ectonucleotide pyrophosphatase/phosphodiesterase family member 2) using a selective inhibitor leads to significant improvement in fibrosis development in mouse models of liver injury and NASH. 116 In addition, autotaxin levels are elevated in the serum of patients with NAFLD and patients with liver cirrhosis as compared with healthy individuals and correlate with the stage of fibrosis. 117 , 118 Consistently, in a model of CCl 4 -induced liver injury in rats, circulating levels of lysophosphatidic acid and autotaxin activity are increased and correlate with the extent of liver fibrosis as well.…”
Section: Role Of Hepatic Stellate Cells In Nonalcoholic Fatty Liver D...mentioning
confidence: 99%